In vitro study on the disinfectability of two split-septum needle-free connection devices using different disinfection procedures - Engelhart, Steffen; Exner, Martin; Simon, Arne (German Medical Science GMS Publishing House, 2015)
This in vitro study investigated the external disinfection of two needle-free connection devices (NFC) using Octeniderm (spraying and wiping technique) vs. Descoderm pads (wiping technique). The split-septum membrane of the NFC was contaminated with >10 CFU . The efficacy of the disinfection at 30 sec. exposure time was controlled by taking a swab sample and by flushing the NFC with sterile 0.9% sodium chloride solution. Disinfection with octenidine dihydrochloride 0.1 g, 1-Propanol 30.0 g, and 2-Propanol 45.0 g in solution was highly effective (CFU reduction ≥4 log) against both microorganisms, whereas the use of 63.1 g 2-Propanol in 100 ml solution led to residual contamination with . Our investigation underlines that (i) in clinical practice disinfection of NFCs before use is mandatory, and that (ii) details of disinfection technique are of utmost importance regarding their efficacy. Our investigation revealed no significant differences between both split-septum NFC types. Clinical studies are needed to confirm a possible superiority of disinfectants with long-lasting residual antimicrobial activity.